Analysis of Risk Factors for Dyslipidemia in Older Adults: A Literature Study - Kadek Irma Meriana; Sarah Handayani (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: In Indonesia, the prevalence of dyslipidemia increases from 9.3% in the 25—34 age group to 15.5% in the 55—64 age group. As individuals age, they become more susceptible to degenerative diseases, including dyslipidemia. This susceptibility is associated with the aging process, which involves declining cellular function, reduced immune system efficiency, and elevated blood lipid levels in older adults. This study aimed to identify risk factors for dyslipidemia, particularly among the elderly. Methods: This study employed a literature review approach following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A total of 40,315 articles were identified using the search keywords “dyslipidemia in the elderly” or “dislipidemia pada lansia.” The inclusion criteria consisted of original research articles that specifically measured cholesterol levels in elderly participants. After screening and eligibility assessment, six articles were identified as relevant to this research objective. Results: The analysis of the selected studies revealed that risk factors for dyslipidemia in the elderly include menopause, unhealthy lifestyle habits (such as smoking, low physical activity, and poor dietary patterns with low fiber intake), diabetes mellitus, and obesity. Conclusion: This review identified several risk factors for dyslipidemia in the elderly, including age, gender, menopause, unhealthy lifestyle behaviors, diabetes mellitus, and obesity.